Ahlussunah Waljama’ah Curriculum Management in Forming Student Characteristics - Masduki; Ahmad Fikri Aziz Masduki; Arfiani Yulianti Fiyul; Ade Jamarudin (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
This research aims to analyze the management of ASWAJA based local content curriculum to build the character of students who are faithful, devout and noble. This is a case study approach descriptive qualitative research, carried out in religious-based educational institutions. Data were collected through interviews, observations, and documentation studies, then analyzed using data reduction. Result of research showed that at the planning stage, the curriculum was designed by determining Aswaja-based subjects, selecting competent teachers, and providing relevant learning resources. Curriculum implementation involves developing a syllabus, preparing lesson plans, and implementing learning methods that integrate Aswaja values. Evaluation is carried out reflectively and summatively to measure the success of curriculum implementation. However, several obstacles such as the lack of innovative learning methods and teacher rotation are challenges that needed to be overcome. This research confirmed that Aswaja values have strategic potential moderate, inclusive, based on local wisdom. For optimization, synergy is needed between educational institutions, the community and the government in ensuring the sustainability of local content curricula as a solution to face the moral crisis in the modern era.